2021
DOI: 10.3389/fpsyt.2021.536257
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Imbalance in Schizophrenia. From Research to Clinic: Potential Implications for Treatment

Abstract: Cytokines are one of the most important components of the immune system. They orchestrate the brain's response to infectious and other exogenous insults and are crucial mediators of the cross-talk between the nervous and immune systems. Epidemiological studies have demonstrated that severe infections and autoimmune disorders, in addition to genetic predisposition, are risk factors for schizophrenia. Furthermore, maternal infection during pregnancy appears to increase the risk of schizophrenia, and proinflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 176 publications
1
40
0
1
Order By: Relevance
“…Thus, the drugs exert additional effects on the already dysfunctional mitochondria, accounting for increased lactate levels and decreased pH observed after chronic antipsychotic drug treatments discussed in the above section. In addition, abnormal oxidative reactions in mitochondria constantly produce reactive oxygen species (ROS) that induce apoptosis [51,52], inflammation [53,54], and mutations in mitochondrial DNA [55], all of which contribute to the pathogenesis of schizophrenia [11,[56][57][58][59]. The production of ROS worsens abnormal energy metabolism and can exacerbate high lactate levels [11].…”
Section: Mitochondria Dysfunction In Schizophreniamentioning
confidence: 99%
“…Thus, the drugs exert additional effects on the already dysfunctional mitochondria, accounting for increased lactate levels and decreased pH observed after chronic antipsychotic drug treatments discussed in the above section. In addition, abnormal oxidative reactions in mitochondria constantly produce reactive oxygen species (ROS) that induce apoptosis [51,52], inflammation [53,54], and mutations in mitochondrial DNA [55], all of which contribute to the pathogenesis of schizophrenia [11,[56][57][58][59]. The production of ROS worsens abnormal energy metabolism and can exacerbate high lactate levels [11].…”
Section: Mitochondria Dysfunction In Schizophreniamentioning
confidence: 99%
“…Contrary to many reports pointing to upregulated levels of IL-1β or IL-1Ra in schizophrenia, other studies found decreased or no significant alterations in the levels of these cytokines [140,145,146]. As such, the results and observations concerning IL-1 cytokines and their receptors are still vastly inconclusive and must be interpreted with caution [147].…”
Section: Il-1r1 In Schizophreniamentioning
confidence: 77%
“…In our study, we show that neurons mount a robust innate cytokine response to ZIKV infection, including a number of cytokines with previously established effects on behavior. A large body of evidence has established that neuroinflammation and inflammatory cytokine signaling is associated with psychiatric disorders, including major depressive disorder (91)(92)(93)(94) and schizophrenia (95)(96)(97). TNF-α is a major pleiotropic cytokine induced strongly in the CNS by ZIKV and other flaviviruses (98)(99)(100)(101).…”
Section: Discussionmentioning
confidence: 99%